2019
DOI: 10.1016/j.heliyon.2019.e01330
|View full text |Cite
|
Sign up to set email alerts
|

KRAS and NRAS pyrosequencing screening in Tunisian colorectal cancer patients in 2015

Abstract: BackgroundMutations in KRAS and NRAS often result in constitutive activation of RAS in the epidermal growth factor receptor (EGFR) signaling pathway. Mutations in KRAS exon 2 (codon 12–13) predict resistance to anti-EGFR targeted therapy in patients with metastatic colorectal carcinoma (mCRC). However, it's currently known that a significant proportion of mCRC have RAS mutations outside KRAS exon 2, particularly in exons 3 and 4 of KRAS and exons 2, 3 and 4 of NRAS. No data about RAS mutations outside KRAS exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 28 publications
(33 reference statements)
8
27
0
Order By: Relevance
“…The mean age of our patients was 55.41 and the most frequent age range was 51 to 64 years, these results were in agreement with Greater Casablanca cancer registry report 2012 and with Jouini et al findings in the Tunisian population [19,20]. The most tissue specimens were from primary tumors, a similar result was reported by Jouini, et al and Lee et al [20,21].The majority of our patients were diagnosed with adenocarcinoma, this result was similar to that reported by Lee et al and Rindi et al [8,21]. We did not find any correlation between the clinical parameters such as age, sex, stage of disease with RAS mutations, our results agreed with the observations of Most of the previous studies [21 -25].…”
Section: Discussionsupporting
confidence: 93%
“…The mean age of our patients was 55.41 and the most frequent age range was 51 to 64 years, these results were in agreement with Greater Casablanca cancer registry report 2012 and with Jouini et al findings in the Tunisian population [19,20]. The most tissue specimens were from primary tumors, a similar result was reported by Jouini, et al and Lee et al [20,21].The majority of our patients were diagnosed with adenocarcinoma, this result was similar to that reported by Lee et al and Rindi et al [8,21]. We did not find any correlation between the clinical parameters such as age, sex, stage of disease with RAS mutations, our results agreed with the observations of Most of the previous studies [21 -25].…”
Section: Discussionsupporting
confidence: 93%
“…We found that the most abundant mutations of codon were G12D and G12V while G13D is the predominant mutation in codon 13. These results are concordant with the local Tunisian studies [30,31,33,37] and the international ones [12,34,36,[38][39][40][41].…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the NRAS mutation rate was 7.3%, similar to the only available Tunisian study which reported 6.9% [37].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Data from 7 European countries showed that mutations in NRAS is predictors of lower response to anti-EGFR MoAbs treatment in CRC 31 . Jouini et al showed that NRAS gene mutated in 6.9% of the 129 Tunisian colorectal cancer specimens 32 . In Finnish stool DNAs, only one patient with rectum adenoma showed NRAS Q61R mutation 24 , while in another cohort of stool samples from Iranian CRC patients, none of them showed NRAS mutation in codon 12, 13 or 61 25 .…”
Section: Discussionmentioning
confidence: 99%